NUMERICAL ANALYSIS OF SPINAL LOADS IN SPONDYLOLISTHESIS TREATMENT USING PEDICLE SCREWS – PRELIMINARY RESEARCH - ZUBRZYCKI, Jarosław; SMIDOVA, Natalia; LITAK, Jakub; AUSIYEVICH, Andrei (Applied Computer Science, 2017)
The aim of this experimental study was to analyse the influence of lumbar stabilisation used in the treatment of spondylolisthesis on the biomechanical properties of the human lumbar spine. FEM models were built on the basis of pre-surgical CT scans, routinely used in medical practice. MIMICS software was used to process the results of the neuroimaging study and to create 3D models. Two models were built: with and without a stabiliser. A static load analysis was performed for a normal upper-body load. The simulations allowed to determine the stresses in the individual discs for both models, with and without the transpedicular stabiliser.